Hydrodeoxygenation of Isoeugenol over Alumina-Supported Ir, Pt, and Re Catalysts - Alda-Onggar M; Maki-Arvela P; Eranen K; Aho A; Hemming J; Paturi P; Peurla M; Lindblad M; Simakova IL; Murzin DY (AMER CHEMICAL SOC, 2022)
Hydrodeoxygenation (HDO) of isoeugenol (IE) was investigated using bimetallic iridium rhenium and platinum rhenium catalysts supported on alumina in the temperature and pressure ranges of 200-250 degrees C and 17-40 bar in nonpolar dodecane as a solvent. The main parameters were catalyst type, hydrogen pressure, and initial concentration. Nearly quantitative yield of the desired product, propylcyclohexane (PCH), at complete conversion in 240 min was obtained with Ir-Re/Al2O3 prepared by the deposition-precipitation method using 0.1 mol/L IE initial concentration. High iridium dispersion together with a modification effect of rhenium provided in situ formation of the IrRe active component with reproducible catalytic activity for selective HDO of IE to PCH. The reaction rate was shown to increase with the increasing initial IE concentration promoting also HDO and giving a higher liquid phase mass balance. Increasing hydrogen pressure benefits the PCH yield.